Le fait divers criminel dans la littérature contemporaine française (1990-2012) - Mahy, Fanny (2013)
Our collective representation of the « fait divers » underwent considerable revision in the early 1980s, as Marine MSili points out: « from being universally decried, denounced and censured, [it] sees its status change to the point of taking on a positive value », even among the intellectual elite. At the same time, according to Dominique Viart, literature takes on a new « transitivity »; it is no longer self-sufficient but requires a direct object, the world. These two developments provide a meeting ground where new and more frequent interactions between literature and the « fait divers » can take place. This thesis builds on these insights but aims more specifically to demonstrate the significance of the changes that the criminal « fait divers » undergoes as it is recycled in contemporary French literature. The sample corpus includes twenty-five representative works, all published in the period from 1990 to 2012. Through an analysis of investigation procedures and their influence, and an exploration that is part literary criminology and part commemoration of the victims, the thesis demonstrates the richness and diversity of the literary « fait divers » today. Indeed, the revival of interest in the topic, in tune with advances in the humanities, has for the most part broken both with the realist aesthetics of the nineteenth century and with the twentieth centurys more playful and experimental approaches. Many writers have also abandoned the traditional paraliterary and media representations of an archaic monstrosity in favour of a broader socio-historical reflection and more pointed questioning of the monstrousness that lies at the very heart of our humanity.